Evaluation of Academic Vitality and Motivation of Students Based on Their Perception of the Learning Environment in Abadan School of Medical Sciences, Iran in 2018 - Jamshid Bahmaei; Rozita Mostatab; Maryam Shomalinejad; Anahita Maleki; Fatemeh mobasheri (Mazandaran University of Medical Sciences, 2019)
Introduction and purpose: The learning environment affects the development and growth of a learner in an educational institution. Academic vitality and motivation are among the determining factors of success in the educational system. Consequently, the purpose of this study was to evaluate the academic vitality and motivation of students based on their perception of the learning environment in Abadan School of Medical Sciences, Iran. Methods: This descriptive-analytical study was performed on the study population of all students of Abadan School of Medical Sciences. The sample size was calculated as 283 people and the samples were selected through simple random sampling method. The data were collected by the researchers using the questionnaires of learning environment evaluation and academic vitality and motivation. All the data were statistically analyzed by Pearson's correlation test and regression test utilizing the SPSS software version 18. Results: Our findings demonstrated that there was a positive correlation between learning vitality and the perception of students of the learning environment. Moreover, the perceptions of students of the learning environment could be predictive of their educational vitality and academic motivation. All the components of the perception of students of the learning environment were able to predict the vitality of students. It should be noted that among the components of perception of the learning environment, only the aspect of the perception of the educational environment had a significant role in predicting academic motivation. Conclusion: According to the results of the present study, a better understanding of students of the learning environment leads to higher motivation toward academic achievement in diverse educational and research fields. Furthermore, the improvement of the learning environment enhances the academic vitality of students in terms of responding to the confronted challenges and obstacles in educational environments.